Análisis de configuraciones de parques fotovoltaicos debido a sombreados parciales - Tinoco Tinoco, Luis Felipe (Universidad Michoacana de San Nicolás de Hidalgo, 2019)
In this thesis the effect of partial shading on the generation of energy of a photovoltaic park of 11.52 MWp is analyzed. The 11.52 MWp park is constitute by 38,400 of 300 Wp photovoltaic modules, which were programmed in Matlab / Simulink. The partial shading in photovoltaic parks, is due to the shadows caused by the clouds that pass over the parks, which cover an extension of between 2 to 3 hectares per MWp. The results obtained in the simulations indicate that the 11.52 MWp park can produce from 40 MWh/day to 83 MWh/day depending on the cloudy conditions, partial nobosity, orientation and/or connection of the modules. Hence the importance of analyzing the configurations that largescale photovoltaic parks should have, in order to obtain the greatest amount of electrical energy produced. The characteristics of the photovoltaic module that was implemented in Matlab / Simulink correspond to a Solartec S72PC-300 which is in operation at the Departamento de Posgrado de Ingeniería Eléctrica de la Universidad Michoacana de San Nicolás de Hidalgo. That´s it, in the studies carried out, the real measurements of solar irradiation of the Posgrado building were used. The model that was implemented in Matlab / Simulink was verified with the own Matlab / Simulink. The model of the Matlab / Simulink was not used in the thesis because it could not be used for studies of partial shading. In the thesis the effects of the configurations of the photovoltaic modules by partial shading conditions are shown, these configurations include the use of bypass diode, series configuration (S), parallel (P), series-parallel (SP), linked bridge (BL), honey-comb (HC) and total Cross-Tied (TCT), being the TCT the one that extracts the most energy from the photovoltaic park before partial overlap conditions.

En la presente tesis se analiza el efecto del sombreado parcial sobre la generación de energía de un parque fotovoltaico de 11.52 MWp. El parque de 11.52 MWp está conformado por 38,400 módulos fotovoltaicos de 300 Wp, los cuales fueron programados en Matlab/Simulink. El sombreado parcial en parques fotovoltaicos, es debido a las sombras ocasionadas por las nubes que pasan sobre los parques, los cuales abarcan una extensión de entre 1.5 a 3 hectáreas por MWp. Los resultados obtenidos en las simulaciones, indican que el parque de 11.52 MWp puede producir de 40 MWh/día a 83 MWh/día dependiendo de las condiciones de nublado, nublado parcial, orientación y/o conexión de los módulos. De aquí la importancia de analizar las configuraciones que deben de tener los parques fotovoltaicos de gran escala, para obtener la mayor cantidad de energía eléctrica producida. Las características del módulo fotovoltaico que se implementó en Matlab/Simulink corresponden a un Solartec S72PC-300 el cual se tiene en operación en el Departamento de Posgrado de Ingeniería Eléctrica de la Universidad Michoacana de San Nicolás de Hidalgo. Así mismo en los estudios realizados, se utilizaron las mediciones reales de irradiación solar del edificio del Posgrado. El modelo que se implementó en Matlab/Simulink fue verificado con el propio del Matlab/Simulink. El modelo propio del Matlab/Simulink no fue utilizado en la tesis por el hecho de no poderse usar para estudios de sombreado parcial. En la tesis se muestran los efectos de las configuraciones de los módulos fotovoltaicos ante condiciones de sombreado parcial, dichas configuraciones incluyen el uso de diodo bypass, configuración serie (S), paralelo (P), serie-paralelo (SP), puente vinculado (BL), honey-comb (HC) y total cruzado (TCT), siendo el TCT el que mayor energía extrae del parque fotovoltaico ante condiciones de sombreado parcial.
Facultad de Ingeniería Eléctrica. Maestría en Ciencias en Ingeniería Eléctrica
Keywords: info:eu-repo/classification/cti/7; FIE-M-2019-0344; Irradiancia; Diodos bypass; Simulaciones; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3543